PEMERIKSAAN LINGKUNGAN BEBAS JENTIK NYAMUK DI KELURAHAN SANGAJI RT8-RT10 - Azzahra, Vanesya Fadlillah; Yusri, Nurmalia; Hamid, Siti Hartina; Sapsuha, Inriyani; Fatah, Safina; Renmaur, Irma; Buton, Riswan; Lestari, Tutik (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Dengue Fever is a disease caused by a virus that is transmitted through mosquito bites. This disease is quite high in cases, especially in tropical areas, the risk factors for transmission vary depending on rainfall, temperature, and level of urbanization. The purpose of this activity is to motivate and empower the community to implement a healthy lifestyle in everyday life. The method of activity is visiting people's homes to check water reservoirs. From the results of the inspection of 20 houses, 14 houses were found to have mosquito larvae in water reservoir locations such as buckets, KM/WC bathtubs, drums, basins, and dispenser stands, while 6 other houses did not show the presence of mosquito larvae. Further activities are needed to increase public knowledge about the importance of eradicating mosquito nests and optimizing the 1 house 1 mosquito larvae movement.